Low prevalence of primary biliary cirrhosis in Victoria, Australia. Melbourne Liver Group. Issue 6 (June 1995) - Watson, R G; Angus, P W; Dewar, M; Goss, B; Sewell, R B; Smallwood, R A
Abstract : A prevalence study of primary biliary cirrhosis was carried out in the state of Victoria, Australia, by means of a mail survey of specialist physicians and a review of hospital records. Eighty four cases were identified, giving a prevalence of 19.1 per million population (95% confidence limits (CI) 15.3, 23.7), which is among the lowest in published reports. The prevalence in the Australian born, at risk population (women over the age of 24) was 51 per million (95% CI 37.5, 67.9). Both these figures are considerably lower than those in populations of similar age distribution in the UK and northern Europe. Since most Victorians are descended from British or European settlers, the low prevalence of primary biliary cirrhosis in this study supports the hypothesis that local environmental factors may be important in the pathogenesis of this disease.